PENGARUH LINGKUNGAN KERJA FISIK DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DINAS PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK DAN KELUARGA BERENCANA (DP3AKB) PROVINSI JAWA BARAT PADA JABATAN PELAKSANA - Ernawati Intan Amilia; Aam Rachmat Mulyana (ITB AAS Indonesia Surakarta, 2025)
The increasing number of cases of violence against women has made West Java Province the province with the highest number of cases of violence against women nationally, according to the 2024 annual report of the National Commission on Violence Against Women (Komnas Perempuan). Employees of the West Java Provincial DP3AKB are at the forefront of handling cases of violence, with various tasks under their purview. The complexity of these tasks requires professionalism, empathy, and supportive working conditions both physically and psychologically, making job satisfaction a crucial element. The purpose of this study is to determine the influence of physical work environment and work load on the job satisfaction of DP3AKB staff. This study is a descriptive quantitative study using three variables. The data used consists of primary data from a survey of 66 participants and secondary data from literature reviews. The data was analyzed using descriptive statistics, classical assumption tests, and hypothesis testing. The results of this study indicate that the physical work environment and workload, both separately and together, have a positive influence on the job satisfaction of DP3AKB employees.